2013
DOI: 10.2119/molmed.2013.00151
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin Effect on Endothelial Monocyte Activating Polypeptide II (EMAP-II)-Associated Lymphocyte Cell Death and Metastases in Colorectal Cancer Patients

Abstract: Kisspeptin is an antimetastatic agent in some cancers that has also been associated with lymphoid cell apoptosis, a phenomenon favoring metastases. Our aim was to determine the association of kisspeptin with lymphocyte apoptosis and the presence of metastases in colorectal cancer patients. Blood was drawn from 69 colon cancer patients and 20 healthy volunteers. Tissue specimens from healthy and pathological tissue were immunohistochemically analyzed for kisspeptin and endothelial monocyte activating polypeptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
1
4
0
3
Order By: Relevance
“…Summarizing the results obtained, it can be argued that kisspeptin-54 is directly involved in the regulation of PBMC apoptosis, which is obviously an important mechanism for controlling the activation of these cells during pregnancy. Stathaki, M. and co-authors also showed that kisspeptin-54 induces apoptosis of lymphocytes in vitro [14]. In addition, we have shown that kisspeptin-54 promotes the formation of peripheral tolerance by stimulating IDO activity.…”
Section: Modulation Of Ido Activity By Kisspeptin-54supporting
confidence: 62%
“…Summarizing the results obtained, it can be argued that kisspeptin-54 is directly involved in the regulation of PBMC apoptosis, which is obviously an important mechanism for controlling the activation of these cells during pregnancy. Stathaki, M. and co-authors also showed that kisspeptin-54 induces apoptosis of lymphocytes in vitro [14]. In addition, we have shown that kisspeptin-54 promotes the formation of peripheral tolerance by stimulating IDO activity.…”
Section: Modulation Of Ido Activity By Kisspeptin-54supporting
confidence: 62%
“…The KP/GPR54 signaling pathway plays an important role in initiating the secretion of gonadotropin-releasing hormone (GnRH) at puberty, and is involved in the regulation of the GnRH/GnRH receptor (GnRHR) signaling pathway (6). Previous research has provided substantial evidence supporting the role of the KISS-1/GPR54 signaling pathway in the regulation of the reproductive axis, including the timing of puberty, the sexual differentiation of the brain, the regulation of GnRH at puberty, as well as in diabetes, adiposity, atherogenesis (7), gastrointestinal motility (8), learning and memory (9), and suppression of metastasis across a range of cancer types (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…EMAP II could suppress the growth of primary and metastatic tumors and induce apoptosis in growing endothelial cells ( Schwarz et al, 2010a ). Elevated EMAP II expression was associated with lymphocyte apoptosis and lack of metastases in colon cancer patients ( Stathaki et al, 2014 ). The in vivo study reported that EMAP II attenuated the primary tumor growth of rat C6 glioma cells ( Schwarz and Schwarz, 2004 ).…”
Section: Introductionmentioning
confidence: 99%